Hippuric acid in urine: reference values - Siqueira,Maria Elisa PB (2002)
OBJECTIVE: To establish reference values for hippuric acid (HA) excreted in the urine, and to evaluate the impact of age, gender, alcohol, and tobacco, on these levels in a population nonexposed to toluene. METHODS: Reference values for hippuric acid in urine were determined in 115 toluene nonexposed healthy volunteers, from Alfenas city, Southeastern Brazil. A questionnaire was applied to each volunteer and data on occupational and personal habits were collected. Biochemical and hematological analyses were used to confirm the volunteers' good health condition. Reference values were expressed in g HA/g urine creatinine, as mean ± standard deviation (x ± SD), median, 95% confidence interval (95%CI), 95th percentile, and upper reference value (URV, mean +2 SD). RESULTS: Reference values of hippuric acid in urine were: mean ± standard deviation =0.18±0.10; median =0.15; 95% confidence interval =0.16±0.20; 95th percentile = 0.36 and upper reference value (URV, mean +2 SD) =0.38. Statistically significant differences in urinary HA (Wilcoxon - Mann/Whitney, p<0.05) were observed for different genders and age groups. Alcohol ingestion and smoking habit did not significantly affect the results. CONCLUSIONS: The reference values of hippuric acid in urine can be used in biomonitoring programs of workers occupationally exposed to toluene, especially in the southern region of the state of Minas Gerais. Age and gender may affect the HA reference values.